PENGARUH KEPEMIMPINAN, DISIPLIN KERJA DAN REWARD TERHADAP KINERJA PERANGKAT DESA MELALUI KOMITMEN KERJA (Studi Kasus Kantor Desa Curah kalak, Palangan, dan Kumbangsari Kecamatan Jangkar Kabupaten Situbondo) - Ach. Syamsul Hadi; Triska Dewi Pramitasari; Lusiana Tulhusnah (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This study aims to analyze the influence of leadership, work discipline, and reward on the performance of village officials, with work commitment as a mediating variable. The background of this research is the performance gap phenomenon and the importance of human resource management in the village government sector, specifically in Curah Kalak Village, Palangan Village, and Kumbangsari Village, Jangkar District, Situbondo Regency. A quantitative approach with an explanatory design was employed. The research population included all 35 village officials from the three villages, who also served as the sample using a total sampling technique. Primary data were collected through questionnaires. Data analysis was conducted using Partial Least Squares – Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0, covering convergent validity, reliability, classical assumptions (multicollinearity and normality), Goodness of Fit, coefficient of determination, structural equation analysis, and hypothesis testing. The research findings indicate that leadership has a positive and significant influence on the performance of village officials. However, leadership, work discipline, and reward do not have a significant influence on work commitment. Furthermore, work discipline, reward, and work commitment also do not significantly affect the performance of village officials. Additionally, work commitment was not proven to be a significant mediating variable between leadership, work discipline, or reward and performance. These findings suggest that while direct leadership plays a crucial role, the factors of discipline, reward, and work commitment require re-evaluation in their implementation to significantly contribute to improving the performance of village officials.